Pengaruh Pendidikan Dan Kreativitas Kerja Terhadap Prestasi Kerja Guru : Studi Pada Guru SMP Negeri 6 Bangkalan - Nur Amir Zamroni; Nugroho Mardi W; Chamariyah Chamariyah (Journal of Management and Creative Business, 2024)
This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 45 teachers. The purposes of this study are 1) To test and analyze whether education has a direct effect on teacher performance at SMP Negeri 6 Bangkalan. 2) To test and analyze whether education has a direct effect on teacher motivation at SMP Negeri 6 Bangkalan. 2) To test and analyze whether work creativity has a direct effect on teacher performance at SMP Negeri 6 Bangkalan. 3) To test and analyze whether motivation has a direct effect on teacher performance. The results showed that: 1) Education had a significant positive effect on teacher performance at SMP Negeri 6 Bangkalan with an original sample value of 0.151. 2) Work creativity has a significant positive effect on teacher performance at SMP Negeri 6 Bangkalan with an original sample value of 0.084. 3) Motivation has a significant positive effect on teacher performance at SMP Negeri 6 Bangkalan with an original sample value of 0.736.